Respect Training of Instructional Design Development for Teachers to Prevent Bullying in Elementary Schools - Ariefa Efianingrum (LPPM UNY, 2011)
The purpose of this study was to develop an instructional design and respect training modules for teachers and school principals to create conducive school cultures, seed non-violence values, and prevent bullying in the elementary school. The study was development research using Thiagarajan’s Four-D model consisting of the four stages of define, design, develop, and disseminate. This present study was limited on the first three stages of the model. The subjects of the study were elementary school teachers and principals in Sleman District. The results of the define stage showed that there had been various forms of violences that happened in schools. At the design stage, the instructional design of training was developed based on the competence standards and basic competencies that were expected to be mastered by school teachers and principals. The design included all ability aspects of cognitive, affective, and psychomotor. At the development stage, expert appraisals/ judgments and trial training were conducted. The Kirk Patrick’s model of training program evaluation showed that the respect training not only transferred knowledge of cognitive aspect, but also the transferred values as affective aspects, as well as developing the skills of participants in applying the respect attitudes into practice in school life.